Organizational culture: a systematic review - Addisalem Tadesse Bogale; Kenenisa Lemi Debela (Cogent Business & Management, 2024)
Organizational inefficiency and ineffectiveness are often linked to identity crises within the organizational context. This systematic review seeks to enhance the comprehension of Organizational Culture (OC) as a crucial approach to addressing such crises. The study focusses on the measurements, perspectives, and orientations of OC, providing comprehensive analyses of recent research on the subject. Employing a systematic literature review methodology, rigorous screening criteria were applied to select articles from reputable databases, such as Science Direct, Elsevier, Taylor & Francis, JSTOR, Emerald, Springer, Wiley, SAGE, and Google Scholar. A total of 52 articles, meeting the defined selection criteria, underwent thorough review and analysis, yielding valuable insights. The findings emphasize the significant impact of OC on workplace dynamics, influencing employee interactions, treatment, and management. The dimensions most frequently explored within OC include innovation, teamwork, result orientation, masculinity, involvement, and power distance. This review delves into the existing literature on the creation and modification of OCs, utilizing three distinct perspectives: functional, leader-trait, and culture transfer. Cultural orientations are categorized into four main groups: workplace orientation, business orientation, system orientation, and group orientation. In conclusion, this study identifies limitations in current research and proposes potential future research directions, thereby contributing to the ongoing discourse on organizational culture and its implications for organizational effectiveness and efficiency.
Keywords: 650; Organizational culture; organizational climate; business culture; systematic literature review; Organizational identity